Modelling of material removal rate in EDM of nonconductive ZrO2 ceramic by Taguchi method - Sabur, Abdus; Ali, Mohammad Yeakub; Maleque, Md. Abdul (Trans Tech Publications Ltd., Switzerland, 2013)
Electro discharge machining (EDM) technique, a noncontact machining process, is applied for structuring nonconductive ZrO2 ceramic. A conductive layer of adhesive copper is applied on the workpiece surface to initiate the sparks. Kerosene is used as dielectric for creation of continuous conductive pyrolytic carbon layer on the machined surface. Experiments are conducted by varying the peak current (Ip), pulse-on time (Ton), pulse-off time (Toff) and gap voltage (Vg). Correlating these variables a mathematical model for material removal rate (MRR) is developed using Taguchi method. The optimized parametric conditions are determined for higher MRR through ANOVA and signal to noise (S/N) ratio analysis. The results showed that the Ip and Ton are the significant parameters of MRR in EDM for nonconductive ZrO2 ceramic. The model also showed that MRR increases with the increase of Ip and Ton, but the process is controlled by Ip as a whole.